The Three-Dimensional Debordering of Language Policies by AI Translation: Theoretical Modeling and Multicultural Cases from Complex Adaptive Systems - Bao, Pengfei (Forum for Linguistic Studies, 2025)
This study employs Complex Adaptive Systems (CAS) theory to construct a Technology-Mediated Language Ecology (TMLE) framework, decoding how AI translation technologies restructure language policies through adaptive agent interactions and nonlinear emergence—two core principles of CAS. The TMLE model proposes a three-dimensional analytical framework (geospatial, socio-functional, and semiotic debordering), reimagining language policies as dynamic ecosystems where technological mediation and societal practices co-evolve. Taking the EU’s multilingual governanceand Egypt’s 2023 educational reform on dialectal Arabic as paradigmatic cases, the research demonstrates how adaptive agent coalitions—comprising governments, translation platforms (e.g., DeepL), and grassroots communities—collaboratively dismantle traditional policy boundaries. For instance, in the EU, neural machine translation (NMT) enabled a tripartite interaction among the European Commission, tech developers, and regional language activists, facilitating the rise of non-English languages in official domains. In Egypt, WhatsApp’s auto-transliteration tools, used by students and educators, compelling policymakers to recognize Egyptian Arabic (Masri) in digital literacy curricula, illustrating how bottom-up tech practices and institutional responses form a CAS-driven feedback loop. Through these cases, the study reveals that the traditional "territory-function" paradigm fails due to its static, linear logic, whereas the TMLE model—rooted in CAS’s principles of emergence and adaptive coordination—provides a robust framework for understanding tech-mediated language policy dynamics. The findings call for a shift from state-centric regulatory control to ecosystemic stewardship, where policies act as facilitators of adaptive linguistic networks rather than enforcers of rigid boundaries.